Book reviews. Issue 1 (April 2020) - Carr, Jane
In this section ten books are reviewed, presented in the following general order: children's ministry and families, youth ministry and families, adult ministry and community/small groups, foundations of Christian education, teaching-learning process, spirituality and spiritual formation, and leadership and administration—although reviews may not appear for each area. A list of each area and responsible editors appears after the last review in this section. We invite readers to consider reviewing a book for CEJ. Guidelines are available in downloadable documents atwww.biola.edu/cej under Publications Policy on the drop-down menu.